Comparative Analysis of Final Presidential Debate Closing Statements:: Anies Baswedan, Prabowo Subianto and Ganjar Pranowo - Nurchaerani, Meiyanti; Maella, Nurannafi Farni Syam; Prasetyo, Iwan Joko; Alfian, Alfian (Journey: Journal of English Language and Pedagogy, 2024)
This paper analyzed the closing statements of three presidential candidates in Indonesia: Anies Baswedan, Prabowo Subianto, and Ganjar Pranowo. Through a comparative qualitative examination, communication strategies and leadership qualities were evaluated. The objective of this study is to identify the key themes and rhetorical strategies employed by Anies Baswedan, Prabowo Subianto and Ganjar Pranowo in their closing statements; and second, to assess the effectiveness of these strategies in conveying leadership qualities and policy priorities to the electorate. The closing statements of the candidates were transcribed verbatim from recorded debate session. The primary instrument used for data collection was audio/video recordings of the final presidential debate. In conclusion, effective communication played a pivotal role in shaping public perception and influencing electoral outcomes by understanding the nuances of each candidate's rhetorical strategies, future research can provide valuable insights for political communication and leadership in Indonesia.